Efficiency and demographics of a high-yield dairy ewe farm with two managing systems involving five or 10 lambings per year. (9th January 2018) - Pesantez-Pacheco, J.-L.; Torres-Rovira, L.; Hernandez, F.; Sanz-Fernandez, M. V.; Villalobos, N. P.; Heras-Molina, A.; Garcia-Contreras, C.; Vazquez-Gomez, M.; Martinez-Ros, P.; Gonzalez-Martin, J.-V.; Gonzalez-Bulnes, A.; Astiz, S.
Abstract : This study assessed milk productivity, demographic characteristics and workload distribution on a single high-yield dairy ewe farm in Spain (Avila, Spain; continental climate, latitude of 40.90 N, altitude of 900 m) over a 7-year period considering a transition from a herd management system involving five lambings per year (5LY) to a system involving 10 lambings per year (10LY). The 5LY system was practiced on the farm from 2010 to 2012 and the 10LY system from 2014 to 2015, with 2009 and 2013 being considered transition years. During this period, 27 415 lactations were recorded from an average of 3746 Lacaune sheep/year. Several productivity parameters were higher in 2014 to 2015 than in 2010 to 2012: milk yield/lactation (370±156 v. 349±185 l), lactation length (218±75 v. 192±75 days) and dry period length (53.5±38.3 v. 69.1±34.8 days) (all P <0.0001). During 2014 to 2015, investment in new lambing facilities was possible, workload was distributed more uniformly throughout the year, workload per worker was smaller, rate of ewe culling was lower (35.39±0.53% v. 42.51±7.51%), ewe longevity was greater and higher-order lactations were more numerous ( P <0.0001). On the other hand, during 2010 to 2012, daily production was higher (1.73±1.66 v. 1.70±0.62 l/day; P =0.038), the interlambing period was shorter (283±50 v. 302±44 days; P <0.0001) and lambings/ewe per year were greater (1.42±0.01 v. 1.30±0.01; P <0.05). These results suggest that a 10LY herd management system can be compatible with profitability, productivity and good animal and worker's welfare on a high-yield dairy farm, and may even be associated with better outcomes than a 5LY system.